Pelatihan Membangun Media Evaluasi Pembelajaran Menggunakan Quizziz pada Guru dan Dosen Perkumpulan Profesi Multimedia dan Teknologi Informasi (PPMULTINDO) - Sindhu Rakasiwi; Cahaya Jatmoko; Candra Irawan; Lalang Erawan; Suprayogi Suprayogi; Deddy Award Widya Laksana (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to provide insight and training to teachers and lecturers who are members of the Multimedia and Information Technology Professional Association (PPMULTINDO) regarding the use of the Quizizz application as a learning evaluation medium. The background of this activity is that there is a challenge for educators to continue to innovate in the digital era, but there are still obstacles in the form of a lack of introduction and insight into Quizizz, as well as the assumption that the development of technology-based evaluation media is complicated. This training was carried out online through the Zoom application with tutorial, guidance, and consultation methods. The results achieved are that the trainees gain basic understanding and skills in using Quizizz to support a more effective and interactive learning process. This activity is expected to motivate teachers and lecturers to develop technology-based evaluation media and contribute to the advancement of education in the future.